2019
DOI: 10.1051/e3sconf/201912808002
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and numerical analysis of the fluid flow in a mechanically agitated vessel

Abstract: The mixing process is a widespread phenomenon, which plays an essential role among a large number of industrial processes. The effectiveness of mixing depends on the state of mixed phases, temperature, viscosity and density of liquids, mutual solubility of mixed fluids, type of stirrer, a what is the most critical - the shape of the impeller. In the present research, the objective is to analyse the process of the fluid flow in the mechanically agitated vessel with new impeller type. Velocity field values were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Because of the high risk of the hopper formation and turbulence, in mixers quite often the baffles are used (usually two to four), which separate stirring areas. Researchers obtain a very good agreement between experimental and predicted mixing time over a wide range of impellers geometries or diameter and in the area of number blades, blade width and blade angle [3,4]. Thus, in addition to the stirred vessel geometry, the number, shape and position of the blades also have a significant impact on the power, efficiency and quality of mixing.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Because of the high risk of the hopper formation and turbulence, in mixers quite often the baffles are used (usually two to four), which separate stirring areas. Researchers obtain a very good agreement between experimental and predicted mixing time over a wide range of impellers geometries or diameter and in the area of number blades, blade width and blade angle [3,4]. Thus, in addition to the stirred vessel geometry, the number, shape and position of the blades also have a significant impact on the power, efficiency and quality of mixing.…”
Section: Introductionmentioning
confidence: 91%
“…Authors showed that the homogenisation process for mixture in a stirred vessel with rotation impeller without baffles does not require much electrical power. Jaszczur et al [4] analysed the process of the fluid flow in the mechanically agitated vessel without baffles with new impeller type versus the Rushton turbine. The authors, as the basis for the assessment of the intensity degree and efficiency of mixing, used the analysis of velocity vectors distribution and power number.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results showed that flow pattern and dimensionless velocity distribution are related to Reynolds number and regime type without change values in the turbulent regime. The lowest drop of total power number for single and parallel configuration of the impellers was observed in laminar regime [5,6,78,79,164]. A large number of researchers have performed numerical simulations to examine the impact of impeller geometry on the mixing process in order to find optimal configuration, low mixing time or low power consumption [165][166][167].…”
Section: The Effect Of Impellersmentioning
confidence: 99%
“…the internal vessel geometry or configuration (baffles, coils, vessel bottom type, etc. [3][4][5][6]); -the fluid properties (densities, number of phases, a viscosity [7]);…”
Section: Introductionmentioning
confidence: 99%